Auditor Dysfunctional Behavior, Impact of Auditor Competence, Time Budget Pressure and Obedience Pressure - Listiarini, Niken Dwi; Srimindarti, Ceacilia (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The purpose of this study is to empirically examine the impact of auditor competence, time budget pressure, and obedience pressure on auditor dysfunctional behavior. Auditor dysfunctional behavior reflects deviant actions that can reduce audit quality, such as manipulation of procedures or manipulation of reports. The population of this study were auditors working at Public Accounting Firms (KAP) in Semarang City, with data collection techniques using questionnaires and multiple linear regression analysis methods. The results of the study indicate that auditor competence and time budget pressure have a positive and significant effect on auditor dysfunctional behavior. This means that auditors who are competent but face time pressure tend to deviate from audit procedures. Meanwhile, obedience pressure shows a positive but insignificant direction, indicating that pressure from superiors or clients is not strong enough to trigger dysfunctional behavior. This finding suggests that organizations need to balance between improving competence and managing auditor work pressure in order to maintain audit quality. This study also suggests the need for ethics and time management training to minimize dysfunctional behavior in environmental audits.